The effect of silver nitrate on the excitation of some secondary metabolite compounds of Melia azedarach L. ex vivo. (Journal of the College of Basic Education, 2022)
This project was conducted in the plant tissue culture laboratory, Biology Department, College of Science, Al-Mustansiriyah University. The major objective of this study was to increase some secondary metabolites using Silver nitrate as abiotic elicitors added to the tissue culture medium of Melia azedarach L. plants. The productivity was compared with those produced by the intact plants. Plant leaves were disinfected by NaOCl at 1% for 5 min. Callus was initiated on leaves explants grown on MS medium supplemented with 2,4-Dichlorophenoxy acetic acid (2,4-D) at concentrations 1.0 mg/l. The same combination was used for callus maintenance. The quality and quantity of phytochemicals were investigated using methanol extracts of leaves and Callus tissues were analyzed using High Performance Liquid Chromatography (HPLC). Results showed an increase of secondary metabolites concentration in methanol extracts of callus cultures compared with leaves extract. Callus cultures were treated with silver nitrate (AgNO3) at the concentrations 0.1, 0.2, 0.3 or 0.4 mM. Results also showed all concentration of secondary metabolites were increased. P-hydroxy benzoic acid , Azadirachtin were recorded significant differences compared with control, reached 0.0616, 0.7262 mg\g respectively. While p-cinamoylmelianolone , 1-cinnamoyl-3,11-dihydroxy meliacarpin and Salanin concentration reached 0.0787, 0.1821 and 0.1179 mg\g respectively but not recorded significant differences. Results also showed that using silver nitrate caused decrement of fresh and dry weight without any significant differences compared to control.